2011
DOI: 10.1021/np200499d
|View full text |Cite
|
Sign up to set email alerts
|

Antiplasmodial and Antiproliferative Pseudoguaianolides of Athroisma proteiforme from the Madagascar Dry Forest

Abstract: Investigation of extracts from the plant Athroisma proteiforme (Humbert) Mattf. (Asteraceae) for antimalarial activity led to the isolation of the five new sesquiterpene lactones 1–5 together with centaureidin (6). The structures of the new compounds were deduced from analyses of physical and spectroscopic data, and the absolute configuration of compound 1 was confirmed by an X-ray crystallographic study. Athrolides C (3) and D (4) both showed antiplasmodial activities with IC50 values of 6.6 (3) and 7.2 μM (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…Compound Class/Name EE DCME ACNE helichrysoside [51] + quercetin [40] + + tiliroside [52] + tiliroside analog [52] + kaempferol [41] + chalcone arenariumoside V [53], arenariumoside VI [53], arenariumoside VII [53] + tomoroside A [53] + isosalipurposide [40] + helilupolone [54] + Terpenoid sesquiterpenoid sesquiterpene derivative [55][56][57] + sesquiterpene derivative [55][56][57] + sesquiterpene derivative [58][59][60] + sesquiterpene derivative [61,62] + sesquiterpene derivative [62][63][64] + eudesmane derivative [65] + sesquiterpene derivative [66][67][68] + sesquiterpene derivative [66][67][68] + ainsliaside E [69] + cinnamoyloxy-hydroxyeudesmane [70] + athrolide C [71] + + athrolide D [71] + diterpenoid diterpene derivative [30,72] + 8-(acetyloxy)-3-ethenyloctahydro-10-hydroxy-3,4a,7,7,10a-pentamethyl-1H-naphtho[2,1-b]pyran-2,5(3H,4aH)-dione [72] + (7-ethenyl-1,2,3,4,4a,4b,5,6,7,8,10,10a-dodecahydro-1,4a,7-trimethyl-1-phenanthrenyl)methyl-butanedioic acid methyl ester [72] + ent-kaurane derivative [73] + gymnospermin …”
Section: Nomentioning
confidence: 99%
“…Compound Class/Name EE DCME ACNE helichrysoside [51] + quercetin [40] + + tiliroside [52] + tiliroside analog [52] + kaempferol [41] + chalcone arenariumoside V [53], arenariumoside VI [53], arenariumoside VII [53] + tomoroside A [53] + isosalipurposide [40] + helilupolone [54] + Terpenoid sesquiterpenoid sesquiterpene derivative [55][56][57] + sesquiterpene derivative [55][56][57] + sesquiterpene derivative [58][59][60] + sesquiterpene derivative [61,62] + sesquiterpene derivative [62][63][64] + eudesmane derivative [65] + sesquiterpene derivative [66][67][68] + sesquiterpene derivative [66][67][68] + ainsliaside E [69] + cinnamoyloxy-hydroxyeudesmane [70] + athrolide C [71] + + athrolide D [71] + diterpenoid diterpene derivative [30,72] + 8-(acetyloxy)-3-ethenyloctahydro-10-hydroxy-3,4a,7,7,10a-pentamethyl-1H-naphtho[2,1-b]pyran-2,5(3H,4aH)-dione [72] + (7-ethenyl-1,2,3,4,4a,4b,5,6,7,8,10,10a-dodecahydro-1,4a,7-trimethyl-1-phenanthrenyl)methyl-butanedioic acid methyl ester [72] + ent-kaurane derivative [73] + gymnospermin …”
Section: Nomentioning
confidence: 99%
“…SQLs are naturally occurring plant terpenoids that are used for taxonomic analysis (Seaman 1982). Many biological activities have been described for the A. confertiflora SQLs, including larvicidal, antimicrobial, antifungal, antiplasmodial and antiproliferative activities (Picman 1986;Pan et al 2011;Robles et al 2011;Duraipandiyan et al 2012;de la Torre et al 2013;Salazar et al 2014). Earlier studies on the aerial parts of A. confertiflora reported more than 12 SQLs (Yoshioka et al 1970); mycobacterial inhibition has been reported for some of these SQLs (Fischer et al 1998).…”
Section: Research Articlementioning
confidence: 99%
“…Compounds 5 and 6 displayed moderate antiproliferative activity against the A2780 human ovarian cancer cell line, with IC 50 values of 4.1 and 2.7 µM, respectively. 3) Two new dibromo proaporphine alkaloids, saldedines A (8) and B (9), were isolated from the DCM fraction of an unidentified Didemnidae tunicate collected at Salary Bay, Madagascar. These two compounds were reported to be the first two marine proaporphine alkaloids.…”
Section: Alkaloidsmentioning
confidence: 99%
“…In particular, compound 26 exhibited selective antiplasmodial activity (IC 50 value of 4.4 µM) with very low cytotoxicity (selectivity index of about 50). 9) 3. Terpenoids and Steroids 3.1.…”
Section: Alkaloidsmentioning
confidence: 99%